Hubungan indikator antropometri dengan kadar kolesterol total pada wanita usia subur - Nurmina Kaimudin; Rosdiana Mus; Jansye Cynthia Pentury Pentury; Mutmainnah Abbas; Vina Zakiah Latuconsina (Poltekkes Kemenkes Aceh, 2025)
Background: Total cholesterol in the blood that can experience increased or hypercholesterolemia. Risk factors for hypercholesterolemia such as poor lifestyle. Reproductive women usually tend to have a poor lifestyle and diet, resulting in an increase in total cholesterol and additional fat in the body which can be mid upper arm circumference (MUAC),and waist circumference (WC) in reproductive Women Objectives: To determine the relationship between WC and total cholesterol and determine the relationship between MUAC and total cholesterol in reproductive womenMethods: . This study used observational analytical design and purposive sampling techniques. The study was conducted in Tahoku Hamlet in March with a total of 81 samples that met the inclusion criteria including reproductive age women 15-35 years, subjects willing to sign informed consent, not suffering from DM and heart disease, not pregnant and breastfeeding, fasting 8-12 hours, not smoking and consuming alcohol. The data were analyzed with kolmogorov smirnov and spearman correlation tests.Results: The results showed no significant relationship between WC and total cholesterol (p=0.184) and no significant relationship between MUAC and total cholesterol (p=0.666).Conclusion: No significant relationship between MUAC and total cholesterol in reproductive women